Price Adjustment of Oil Palm and Palm Oil in Thailand to the World Price of the Palm Oil Market - Saleerut, Sriwena; Jatuporn, Chalermpon; Suvanvihok, Vasu; Wanaset, Apinya (Asian Journal of Agriculture and Rural Development, 2020)
The objectives of this study are to analyze: (1) the effects from the change of palm oil price in the world market to the prices of oil palm and palm oil in Thailand, and (2) the adjustment of oil palm and palm oil prices in Thailand to the change of the price of palm oil in the world market using monthly time series from January 2008 to September 2019. The statistics consist of the stationary test using the ADF unit root, the long-run equilibrium test using the cointegration, and the short-run adjustment to the equilibrium using the error correction model, respectively. The empirical findings show that farm-gate price is the most affected by the change of palm oil price in the world market, followed by wholesale, export, and retail prices, respectively. In line with the adjustment of the prices of oil palm and palm oil in Thailand to the change in the world palm oil price, it is found that farm-gate price has adjusted in the short-term to return the equilibrium with the highest speed at 27.883%, followed by wholesale price 22.710%, exporting price 18.792%, and retail price 15.658%, respectively.